Use of polymerase chain reaction and rabbit infectivity testing to detect Treponema pallidum in amniotic fluid, fetal and neonatal sera, and cerebrospinal fluid. - Grimprel, E (1991)
The diagnosis of congenital syphilis continues to pose a difficult clinical challenge. Because the serodiagnosis of congenital syphilis has significant limitations, the direct detection of Treponema pallidum in suspect neonatal tissues or body fluids represents a desirable alternate diagnostic strategy. We developed and applied the polymerase chain reaction (PCR) for the detection of T. pallidum in clinical material relevant to the diagnosis of congenital syphilis but which typically contain factors inhibitory for the PCR. Four methods of specimen processing were examined to circumvent PCR inhibition; clinical materials included amniotic fluids, neonatal sera, and neonatal cerebrospinal fluids. The PCR was 100% specific for T. T. pallidum compared with the sensitive rabbit infectivity test (RIT) for all clinical materials tested. For amniotic fluids, the PCR was 100% sensitive when correlated with the RIT but had a lesser sensitivity when applied to sera or cerebrospinal fluids, which typically contain few treponemes. The combined sensitivity of the PCR for all clinical samples was 78%. Positive PCR results also were obtained among some clinical specimens for which RIT was not performed; these results correlated well with either stigmata or risk factors for congenital syphilis. The combined results suggest that the PCR can be a useful adjunct to the diagnosis and clinical management of congenital syphilis and that it will provide a valuable tool for investigations of the pathogenesis of the disorder.